Controlling minor outbreaks is necessary to prepare for major pandemics. - Adam J Kucharski (PLoS Biology)
Ongoing influenza H5N1 outbreaks highlight the need for timely, scalable interventions that draw on lessons from COVID-19. In particular, successful pandemic preparedness requires early outbreak management, including effective responses targeting spillovers before there is evidence of human-to-human transmission.